Business Model Canvas: Value Proposition / Nur Ain Mardiah Che Apandi - Che Apandi, Nur Ain Mardiah (2020)
There are nine components existed in the business model canvas (BMC) and the first one is customer segment. Customer Segments defines the groups of people or organization you aim to reach or serve. Every company needs profitable customers in order to survive. The information you may want to predict and test for this section could include age, gender, time spent working, etc. Next step in BMC is value propositions, The Value Proposition is an innovation, service, or feature intended to make a company or product attractive to customers. It is based on a review and analysis of the benefits, costs, and value that an organization can deliver to its customer. It is the reason why customers turn to one company over another. Something to keep in mind is your value propositions can change, as you gather more data from customer interviews